Improving Student’s Vocabulary Mastery by Using Problem-Based Learning in Narrative Text - Elisa Z. Puteri Tamuu; Moon Hidayati Otoluwa; Rahmawaty Mamu (Transbahasa, 2024)
This study employs a quantitative method with a pre-experimental design, specifically the one-group pre-test and post-test. The sample of the study consists of IX.1 class students at SMP Muhammadiyah Tilango, selected due to their low vocabulary skills based on interviews with teachers and researchers. The research aims to analyze the effect of problem-based learning on improving students' vocabulary in narrative texts. Data were collected through vocabulary tests administered before and after the intervention. In addition, observations were conducted from the first to the fourth meeting to assess the effectiveness of the method. The results show a significant improvement in the vocabulary skills of the experimental class compared to the control class, which did not receive any treatment. Data analysis using the t-test reveals that the calculated t-value of 4.108 is greater than the t-table value of 2.119, leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). Thus, it can be concluded that problem-based learning effectively improves students' vocabulary skills. This study implies that the problem-based learning method can be implemented as an effective approach to enhance vocabulary learning in secondary schools.